ETR: Mamasab Bakery / Roshazwani Roslan - Roslan, Roshazwani (2019)
Mamasab Bakery is a bakery business based Cyberjaya, Selangor. We are a new bakery brand which is sell cakes, cookies and brownies. Furthermore, we also offer marinated frozen food such as lamb marinate to expand our business toward the taste and preference of our client, bakery class for our customer for those interested to generate income in bakery line of business.